TEACHING ENGLISH TO YOUNG LEARNERS (TEYL): STRATEGIES AND CHALLENGES - Astuti, Neli; Kalayo Hasibuan (English Education Department of STKIP Pasundan, 2025)
Instructing English to Youthful Learners (TEYL) has ended up a central point in remote dialect instruction as globalization emphasizes the significance of English capability from an early age. This paper examines the hypothetical establishments, compelling methodologies, and challenges of educating English to children matured 3 to 12 a long time. The think about is grounded in a comprehensive writing audit of existing investigate, centering on the integration of intuitively instructing strategies, relevant learning, and the utilize of innovation in TEYL. It talks about key learning hypotheses, counting behaviorism, cognitivism, and sociocultural hypothesis, and their applications in making age-appropriate educating approaches. Moreover, this paper investigates obstructions such as constrained assets, instructor preparing crevices, and differing learner needs whereas displaying arrangements to overcome these issues. The bits of knowledge given point to help teachers, policymakers, and analysts in planning more successful and locks in TEYL programs that cater to the special learning needs of youthful children. By leveraging evidence-based hones and understanding the subtleties of early dialect securing, this paper contributes to the upgrade of TEYL in different instructive settings.